Effectiveness of Using Recycled Plastic Broomstick to Maintain Cleanliness of Classrooms of Grade 12 ABM Strand at Bestlink College of the Philippines, S.Y. 2019–2020 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
In this generation, plastic is an extremely common material; now, it is widely used by everyone worldwide. Bottles are a common plastic item. The problem with plastic is its disposal. Plastic will not be decomposed when it is buried. Although plastic is a useful material, it becomes waste after it is used. Recycling refers to processing used materials into a new product to prevent waste pollution. This topic is serious because it can build one’s knowledge and prevent pollution due to plastic waste; thus, we all can help our society and help people become creative through recycling. The objective of this research was to lessen the number of plastic bottles in our environment and create a new product from this waste. To lessen plastic bottle waste, prevent pollution due to its improper disposal, and create a new item from plastic bottles, we used a descriptive research design for this study. A qualitative method was used in this action research. This study involved 50 Accountancy, Business, and Management strand students. Plastic bottles are scattered everywhere after people use them. Instead of ignoring these wastes, we collected and recycled them to make new products that can be used as cleaning materials. The results of this study showed that the students always keep their classroom clean because of our product; they are willing to clean the classroom because of the cleaning materials we made. This study revealed that recycled plastic broomsticks ensure the cleanliness of the classroom. The results of the study also showed how plastic bottles can be used to lessen the amount of plastic bottle waste. In terms of waste management, the use of recycled plastic broomsticks reduced the waste in the school. We can also save the environment when we make broomsticks. This broomstick is also budget-friendly because we do not need to buy anything to make it; we only have to recycle plastic bottles and use scrap wood. We do not have to spend money, and we can also help our environment.
Keywords: waste management, recycling, decompose